Thinking-feeling with the Earth: Territorial Struggles and the Ontological Dimension of the Epistemologies of the South - Arturo Escobar (Antropólogos Iberoamericanos en Red, 2016)
The theoretical framework of Epistemologies of the South was proposed by Boaventura de Sousa Santos as a way to recognize other different manners to understand the World. This offers a much more relevant role to non-Western views about our existence. Under this framework the present article describes the concept of relational ontologies, which implies different theoretical fundamentals for those who no longer want to be complicit with the silencing of popular knowledges and experiences by Eurocentric knowledge. Responding to the monolithic idea of World or Universe, this article presents a transition towards the zapatist inspiration of pluriverse, a world where many words fit. The article describes several examples of indigenous reactions against the mining practices, which were extended into the ontological occupation of the land. This article also argues that the knowledge offered by the Epistemologies of the South is much deeper for the context of social transformation than the one that usually originates in the academy.